The quantity, quality, and daily distribution of protein supplementation in maximizing muscle hypertrophy induced by resistance training - Pawlina, Mateusz; Ziętara, Karolina; Orzechowska, Aleksandra; Oskroba, Aleksander; Pawełczak, Natalia; Raksa, Karolina; Zielonka, Bartłomiej; Kowalczyk, Ilona; Pawłowski, Piotr; Stawikowski, Cezary (Journal of Education, Health and Sport, 2023)
Introduction and purpose: Resistance training (RT) combined with sufficient protein intake (PI) stimulates muscle hypertrophy. There are many factors determining the influence of PI on muscle hypertrophy. The aim of the study is to analyze the current state of knowledge on protein supplementation in the context of optimizing the effects of RT-induced muscles hypertrophy. Description of the state of knowledge: The quality of protein supplements is a factor that has a significant impact on the degree to which they increase MPS. Protein meals containing all EAAs will stimulate MPS most potently. The most important factor determining the effectiveness of protein supplementation is the amount of protein intake per day in relation to body weight. PI in amounts greater than ~1.6 g/kg b.w./day does not further increase the rate of fat free mass gains induced by RE. Supplementing more protein at breakfast than at dinner is more effective in increasing muscle mass gain in response to RT. Summary: The quantity, quality and source of protien supplements, that are daily administered, are important factors contributing to the efectiveness of the supplementation. Distributing the doses of protein supplement throughout the day and consuming greater amount of protein for breakfast rather than dinner may also be beneficial in terms of augmenting muscle protein synthesis (MPS). Optimizing these conditions is conducive to achieving a positive net protein balance, which result in improving RT-induced muscle mass gain.